1983
DOI: 10.2337/diacare.6.5.493
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to IDDM Regimens: Relationship to Psychosocial Variables and Metabolic Control

Abstract: Thirty-four adolescents (ages 12-14 yr) with IDDM completed a questionnaire assessing regimen adherence over the previous week and psychosocial measures potentially related to adherence. Four aspects of the IDDM regimen were studied: insulin injections, dietary patterns, glucose testing, and exercise. Psychosocial variables included (1) Social Learning Theory measures of diabetes-specific family behaviors and barriers to adherence and (2) more general measures of family interaction. Glycosylated hemoglobin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
1
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(95 citation statements)
references
References 19 publications
2
91
1
1
Order By: Relevance
“…1 Moreover, it is well documented that higher levels of conflict in the family correlate with lower levels of child adherence to the diabetes treatment regimen. [2][3][4][5][6][7][8] General family conflict has been demonstrated to relate to adherence in youth with type 1 diabetes in both cross-sectional studies 3,4,8 and longitudinal, prospective research. 9 In a study of parenting, child development, and diabetes adherence and control, Miller-Johnson et al 10 demonstrated that ratings of increased conflict were directly related to diabetes adherence problems and poorer blood glucose control.…”
Section: Recent Research On General Conflict and Parenting Behavior Imentioning
confidence: 99%
“…1 Moreover, it is well documented that higher levels of conflict in the family correlate with lower levels of child adherence to the diabetes treatment regimen. [2][3][4][5][6][7][8] General family conflict has been demonstrated to relate to adherence in youth with type 1 diabetes in both cross-sectional studies 3,4,8 and longitudinal, prospective research. 9 In a study of parenting, child development, and diabetes adherence and control, Miller-Johnson et al 10 demonstrated that ratings of increased conflict were directly related to diabetes adherence problems and poorer blood glucose control.…”
Section: Recent Research On General Conflict and Parenting Behavior Imentioning
confidence: 99%
“…However, increased parental involvement in diabetes management is also reported to create diabetes-related family conflict [17,18]. Furthermore, high levels of family conflict and low levels of family cohesion and support are associated with poorer metabolic control [19][20][21][22] and poorer adherence [23][24][25][26][27] among adolescents.…”
mentioning
confidence: 99%
“…Diabetes compliance consists of an interdependent network of regimen behaviors, rather than a single behavior such as taking medication. As we have documented elsewhere, 5 diabetes regimen adherence is not a unitary construct, and level of adherence to one aspect of the regimen (e.g., glucose testing) is often unrelated to degree of adherence to other aspects of the regimen (e.g., dietary modification). Thus, it is inappropriate to refer to patients as "good compilers" or "poor compliers"; instead we must refer to levels of specific self-care behaviors as they occur in relation to specific regimen tasks.…”
mentioning
confidence: 99%